ANTROPOLOGI IKHLAS: STUDI PSIKOANALISA SIGMUND FREUD - Encung . (Reflektika, 2016)
This text is just to examine how the individual personal system according to Freud, works to determain did and produce maintaining character of Ikhlas. Fatehrmore, working individual sytem of personal life of person is coinciding with a wearness so, called as people consciousness, in cordence with its progress to achieve high personality to work. In other sides to identify pure works as ikhlas did of person is very difficult. It is why Marx propose real porpuse of work is work its self and he who works to reach a special reachment is not entirely false, but it is just to coincide what finally regard as work it self. Freud as identifying important figure to achieve a person’s personality to act is classifying thre principle individual elemant. Id Ego and Superego. The system of three is combining together to stimulate an action of ditermaining life of individual.